Bioinformatic mapping of a more precise Aspergillus niger degradome - Zixing Dong (Nature Portfolio, 2021)
Abstract Aspergillus niger has the ability to produce a large variety of proteases, which are of particular importance for protein digestion, intracellular protein turnover, cell signaling, flavour development, extracellular matrix remodeling and microbial defense. However, the A. niger degradome (the full repertoire of peptidases encoded by the A. niger genome) available is not accurate and comprehensive. Herein, we have utilized annotations of A. niger proteases in AspGD, JGI, and version 12.2 MEROPS database to compile an index of at least 232 putative proteases that are distributed into the 71 families/subfamilies and 26 clans of the 6 known catalytic classes, which represents ~ 1.64% of the 14,165 putative A. niger protein content. The composition of the A. niger degradome comprises ~ 7.3% aspartic, ~ 2.2% glutamic, ~ 6.0% threonine, ~ 17.7% cysteine, ~ 31.0% serine, and ~ 35.8% metallopeptidases. One hundred and two proteases have been reassigned into the above six classes, while the active sites and/or metal-binding residues of 110 proteases were recharacterized. The probable physiological functions and active site architectures of these peptidases were also investigated. This work provides a more precise overview of the complete degradome of A. niger, which will no doubt constitute a valuable resource and starting point for further experimental studies on the biochemical characterization and physiological roles of these proteases.